2015
DOI: 10.1007/s10722-015-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Japanese aromatic rice (Oryza sativa L.) as revealed by nuclear and organelle DNA markers

Abstract: Aromatic rice (Oryza sativa L.) cultivated in Japan is regionally differentiated by geographical distribution and characteristics. We aimed to characterize the lineage of Japanese aromatic rice using DNA markers. Based on analyses with nuclear SSR markers, we found that Japanese aromatic rice cultivars belong, with one exception, to japonica but showed some differences from authentic japonica and were divided into two clades that were distributed in western and eastern Japan, respectively. Further analyses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This indicates that majority of the BPH populations are similar at Gangavathi whereas two biotypes are quite different. Matin et al, 2012, Wunna et al, (2016, Okoshi et al, (2016), Samal et al, (2014 and Krupa et al, (2017) observed similar kind of variation for Polymorphism Information Content (PIC) value and gene diversity in their experiments and these results are on par with the present investigation…”
Section: Clustering Analysis Of 25 Brown Plant Hoppers With Ssr Markerssupporting
confidence: 86%
“…This indicates that majority of the BPH populations are similar at Gangavathi whereas two biotypes are quite different. Matin et al, 2012, Wunna et al, (2016, Okoshi et al, (2016), Samal et al, (2014 and Krupa et al, (2017) observed similar kind of variation for Polymorphism Information Content (PIC) value and gene diversity in their experiments and these results are on par with the present investigation…”
Section: Clustering Analysis Of 25 Brown Plant Hoppers With Ssr Markerssupporting
confidence: 86%
“…Establishment of phylogenetic relationship of cultivated rice/ landraces with the wild ancestors based on plastid subtype is quite relevant in the context that the plastid region of chloroplast is highly conserved in the course of evolution [ 11 ]. Characterisation of aromatic rices grown in Japan using chloroplast and mitochondrial primers differentiated them into tropical japonica and temperate japonica [ 68 ], as these organelle markers provide more information over a larger evolutionary history of crops [ 69 ]. In the present study, though the collection of landraces are from one particular geographical region i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To classify the archaic grains, sequences corresponding to an insertion or deletion (in/del) of 7 bp in the intron of rps16 (assigned as OsC01, Okoshi et al 2016), an in/del of 69 bp in Orf100 (Takahashi et al 2008), a SNP in a pseudo trnI sequence (14,169; Kumagai et al 2016), and an in/del of 32 bp in the intergenic region between petN an trnC (I-32) in the rice chloroplast genome were obtained (Tang et al 2004) (Table 2). Three nuclear markers included SNPs in each of the promoter regions of qSH1 (Konishi et al 2006), exon 1 of sh4 (Li et al 2006), and one set of in/dels of 4 bp and 221 bp in the intergenic region of rice chromosome number 6 (assigned as the DJ6 region, Hanamori et al 2011).…”
Section: Primer Design and Utilizationmentioning
confidence: 99%